2020
DOI: 10.3390/cancers12092684
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and Noncanonical Roles of Fanconi Anemia Proteins: Implications in Cancer Predisposition

Abstract: Fanconi anemia (FA) is a clinically and genetically heterogeneous disorder characterized by the variable presence of congenital somatic abnormalities, bone marrow failure (BMF), and a predisposition to develop cancer. Monoallelic germline mutations in at least five genes involved in the FA pathway are associated with the development of sporadic hematological and solid malignancies. The key function of the FA pathway is to orchestrate proteins involved in the repair of interstrand cross-links (ICLs), to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 159 publications
(170 reference statements)
0
25
0
1
Order By: Relevance
“…Moreover, it has been shown that polymorphism VNDR1349 in IFNG, which causes an increased production of IFN‐γ in vitro, is associated with an increased risk of AA 90 . Together with TNF‐α, increased levels of IFN‐γ have been found in BM of patients with Fanconi anemia, 91 an inherited BM failure syndrome 92 . However, despite the growing evidence on the possible role of IFN‐γ in AA pathogenesis, no data on the effects of in vivo inhibition of this cytokine are available.…”
Section: Ifn‐γ In Aplastic Anemiamentioning
confidence: 99%
“…Moreover, it has been shown that polymorphism VNDR1349 in IFNG, which causes an increased production of IFN‐γ in vitro, is associated with an increased risk of AA 90 . Together with TNF‐α, increased levels of IFN‐γ have been found in BM of patients with Fanconi anemia, 91 an inherited BM failure syndrome 92 . However, despite the growing evidence on the possible role of IFN‐γ in AA pathogenesis, no data on the effects of in vivo inhibition of this cytokine are available.…”
Section: Ifn‐γ In Aplastic Anemiamentioning
confidence: 99%
“…ATR and CHK1 interface with the FA core complex by phosphorylation events to activate the checkpoint response (4). Downstream of ICL removal, the FA pathway recruits elements of the NER pathway and DSB repair systems homologous recombination (HR) or nonhomologous end joining (NHEJ) to resolve the lesion [96]. (C) Telomere stability depends on an intact shelterin and telomerase complex, including the reverse transcriptase TERT, the RNA template TERC, and DKC1 to protect and replicate telomeric DNA.…”
Section: Trends Trends In In Molecular Molecular Medicine Medicinementioning
confidence: 99%
“…FA pathway involves a bunch of FA proteins and other associated proteins, constituting a system serving for interstrand cross-link (ICL) DNA repair in the S phase (Ceccaldi et al, 2016;Milletti et al, 2020), which coordinates each critical step by interacting with various DNA damage repair (DDR) proteins (Kottemann & Smogorzewska, 2013). ICL is a special type of DNA lesions that are a covalent linkage between opposite strands of double-stranded DNA (Fig.…”
Section: The Function and Working Mechanism Of Fa Pathwaymentioning
confidence: 99%